Exostosis of Rib: Case Report of an Extremely Rare Giant Osteochondroma at an Unusual Site, Radiopathological Correlation with Brief Review of Literature - Jilowa, Sarita; Paliwal, Purnima; Kapur, Arun; Verma, G. C. (Indian Journal of Radiology and Imaging, 2021)
Osteochondromas are common benign tumors developing as an abnormal bony growth in the metaphyseal region. Being more of a developmental anomaly rather than a true neoplasm, they are usually found around the growth plates of long bones such as the knee, hip, and shoulder. These are typically managed conservatively if they are asymptomatic; however, they require excision in symptomatic patients. A 38-year-old woman presented with a huge swelling causing disfigurement measuring 16 × 16 cm on the left side of chest wall. Radiographs and computed tomography scan showed a bony outgrowth at costochondral junction of second rib which was in continuity with the periosteum. Excision via mediastinal sternotomy and left thoracotomy was done. Histopathological features corroborated with the radiological diagnosis of osteochondroma. Osteochondroma should be considered in the differential diagnosis of chest wall tumors. Rib is an extremely rare site of presentation. The cartilaginous cap becomes fully ossified and is lost in longstanding lesions. Huge tumors at such a location can cause irritation of adjacent viscera which can lead to pleural effusion or hemothorax; therefore, a cautious and logical approach to diagnosis is warranted for appropriate therapeutic management.
Keywords: costochondral junction; giant osteochondroma; ribs; solitary exostosis